Ataxia and Seizures despite Phenytoin: A Case Report Highlighting the Importance of TDM and Genetic Influences - Rachel Manoj; Arpita Meher; Jefry Winner G. (Case Reports in Neurological Medicine)
Adverse drug reactions to commonly prescribed medications such as phenytoin, used for seizures, often go undetected due to various factors. This case report highlights a 52-year-old male diagnosed with late-onset epilepsy who was prescribed phenytoin. Despite the standard dosage, the patient experienced toxicity symptoms and a seizure, prompting admission for assessment. Laboratory tests and imaging were inconclusive, leading to a therapeutic drug monitoring (TDM) consultation, which revealed elevated phenytoin levels. Genetic testing for CYP2C9 polymorphisms was not feasible but noted as significant, especially in populations with higher prevalence. Phenytoin was tapered, leading to the patient’s gradual recovery upon discontinuation and transition to valproate. The Naranjo scale predicted potential adverse drug responses (ADRs). This case underscores the significance of TDM, genetic considerations in drug metabolism, and the need to be vigilant in treating epilepsy to prevent such adverse events.